A study of Kibbutzim in Israel reveals risk factors for cardiometabolic traits and subtle population structure. (December 2018) - Granot-Hershkovitz, Einat; Karasik, David; Friedlander, Yechiel; Rodriguez-Murillo, Laura; Dorajoo, Rajkumar; Liu, Jianjun; Sewda, Anshuman; Peter, Inga; Carmi, Shai; Hochner, Hagit
Abstract Genetic studies in isolated populations often increase power for identifying loci associated with complex diseases and traits. We present here the Kibbutzim Family Study (KFS), aimed at investigating the genetic basis of cardiometabolic traits in extended Israeli families characterized by long-term social stability and a homogeneous environment. Extensive information on cardiometabolic traits, as well as genome-wide genotypes, were collected on 901 individuals. We observed that most KFS participants were of Ashkenazi Jewish (AJ) genetic origin, confirmed a recent severe bottleneck in the AJ recent history, and detected a subtle within-AJ population structure. Focusing on genetic variants relatively common in the KFS but very rare in Europeans, we observed that AJ-enriched variants appear in cancer-related pathways more than expected by chance. We conducted an association study of the AJ-enriched variants against 16 cardiometabolic traits, and found seven loci (24 variants) to be significantly associated. The strongest association, which we also replicated in an independent study, was between a variant upstream ofMSRA (frequency ≈1% in the KFS and nearly absent in Europeans) and weight (P  = 3.6∙10-8 ). In conclusion, the KFS is a valuable resource for the study of the population genetics of Israel as well as the genetics of cardiometabolic traits.